2016
DOI: 10.1016/j.jpeds.2015.12.052
|View full text |Cite
|
Sign up to set email alerts
|

Investment in Faculty as Educational Scholars: Outcomes from the National Educational Scholars Program

Abstract: A cademic institutions have strong incentives to develop faculty who are productive researchers, master clinicians, and educators. Forward-thinking institutions are encouraging their educators to become not only stellar teachers, but also productive scholars through peerreviewed dissemination of rigorously developed and evaluated curricular innovations, evaluation tools, and teaching methodologies. This emphasis on evaluation is imperative to ensure that educational programs effectively and efficiently meet th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 11 publications
0
34
0
Order By: Relevance
“…This type of education design and evaluation may increase education-related publications and funding, impacting the institution's reputation and ranking. 8 This study has several limitations. First, these scholarly outcomes described are associations.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This type of education design and evaluation may increase education-related publications and funding, impacting the institution's reputation and ranking. 8 This study has several limitations. First, these scholarly outcomes described are associations.…”
Section: Discussionmentioning
confidence: 92%
“…6 Graduates of the Educational Scholars Program 7 demonstrated engagement in scholarship. 8 However, these faculty development programs require significant in-person training, which has challenges related to travel. Online learning may mitigate these challenges with more flexible learning opportunities, decreased costs, and enhanced access.…”
mentioning
confidence: 99%
“…A previous publication of the outcomes of ESP graduates from 2009 to 2013 16 and unpublished data from a survey of ESP graduates from 2015 to 2019 were reviewed for the percentage of graduates who had delivered workshops.…”
Section: Methodsmentioning
confidence: 99%
“…Participant Behavior Data from the previous publication of the outcomes of ESP graduates from 2009 to 2013 (response rate: 76%) indicated that a mean of 5.7 national peer-reviewed workshops (range: 0-15) had been given and that 74% of respondent graduates had delivered at least one national peer-reviewed workshop. 16 Participants who graduated from ESP in 2015-2019 were surveyed for a separate study in 2019 (unpublished data). Of those graduates, at least 1 year postgraduation (graduation years 2017-2018), 45% responded (17 out of 39).…”
Section: Collaboraɵve Group Workmentioning
confidence: 99%
“…While some faculty pursuing medical education as academic scholarship have additional training in medical education through certificate or degree programs, such as the Education Scholars Program (Jerardi et al, 2016;Baldwin, Gusic and Chandran, 2017), most departments have many faculty members without expertise in these skills, but who participate at varying levels in creating, implementing, and/or evaluating education programs. Faculty need professional development learning opportunities and mentorship for planning, leading, and participating in education research.…”
Section: Challenges In Education Research and Scholarshipmentioning
confidence: 99%